Gender and rural-urban differences in the nutritional status of in-school adolescents in south-western Nigeria (2010)
This study assessed gender and rural/urban differences in height and weight, and the prevalence of stunting, underweight and overweight of school-going adolescents in south-west Nigeria, using 2007 WHO reference values for comparison. The influence of sexual maturity and the socio demographic correlates of growth performance were also examined. In this cross-sectional study, 924 male (51.4%) and 875 female (48.6%) students (1799 in total) aged 10–19 years from eighteen schools in Ibadan (five rural, nine urban public and four urban private) were interviewed and examined. Although males were significantly taller than females (p<0.05) stunting was more pronounced for males, who were 7.5 cm shorter than the 2007 WHO reference, compared with females who were 3.5 cm shorter. Body mass index (BMI) for girls was also greater than for boys (p<0.05) Rural adolescents had lower heights and BMIs compared with those in urban areas. The mean height of male adolescents in rural schools fell below 2 SDs of the 2007 WHO reference between 14 and 17 years, while heights of males and females in private schools were similar to the median 2007 WHO standard. Low height-for-age was observed in 282 adolescents (15.7%), which, after multivariate analysis, was significantly associated with school type, gender, number of mother’s children and puberty onset. Adolescents in rural schools were much more likely to be stunted than those in urban private schools (AOR 13.1; 95% CI 5.2–33.2) and males were three times more likely to be stunted compared with females (AOR 3.3; 95% CI 2.4–1.4). Low BMI-for-age was observed in 240 adolescents (18.9%), with correlates similar to stunting. Adolescents at the pre-puberty stage were twice as likely to have low BMI-for-age (OR 2.0; 95% CI 1.6–2.5) than those with signs of puberty. There were 2.3% overweight adolescents, who were significantly more likely to be female, in private school and post-pubertal. Innovative interventions for Nigerian adolescents, especially rural inhabitants and males, are needed to reduce the prevalence of stunting and underweight